1980
DOI: 10.1159/000172777
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Sieve in Renal Glomerular and Tubular Basement Membranes as Revealed by Electron Microscopy

Abstract: Bovine glomerular basement membrane (GBM) was isolated and purified according to a modification of Spiro’s method. Rat and bovine tubular basement membranes (TBM) were isolated and purified by sonic disruption or by the method of Carlson et al. Electron microscopic studies on the ultrastructure of GBM and TBM were performed after negative staining with 1% phosphotungstic acid solution, pH 7.3. When negatively stained, GBM and TBM were seen as fragments varying in size. The surface of the membranes showed a cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

1981
1981
2011
2011

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 6 publications
2
21
0
Order By: Relevance
“…In our earlier studies [19][20][21], we demon strated the fine meshwork structure in GBM which previously had been postulated by physiologists [1,24] and indirectly inferred from tracer experiments [5,7]. It now seems clear that TBM has a similar meshwork structure which may play an important role as reabsorption barrier to proteins.…”
Section: Ligler and Robinsonsupporting
confidence: 56%
See 2 more Smart Citations
“…In our earlier studies [19][20][21], we demon strated the fine meshwork structure in GBM which previously had been postulated by physiologists [1,24] and indirectly inferred from tracer experiments [5,7]. It now seems clear that TBM has a similar meshwork structure which may play an important role as reabsorption barrier to proteins.…”
Section: Ligler and Robinsonsupporting
confidence: 56%
“…Fragments with larger pore sizes showed more variation within each frag ment. The real size might differ from these measured values because, as discussed be low, the shape of pores seen on a micrograph is a projection of a three-dimensional frame work to a piece of film, and the larger value obtained may correspond to the larger di mension of an obliquely sectioned channel as discussed in the previous paper [21]. An interesting finding is shown in figure 5.…”
Section: Resultsmentioning
confidence: 69%
See 1 more Smart Citation
“…Ultrastructures of proximal and distal TBM are likely to differ, because functions of the tubules are different in each segment. In purified rat TBM, we previously have demonstrated a fine meshwork structure similar to that of the GBM [7,11]. Pores in the meshwork of the TBM were larger than in the GBM.…”
Section: Introductionmentioning
confidence: 87%
“…Electron microscopic observations of purified unfixed bovine, rat and human GBM by conventional negative staining, revealed that a threedimensional meshwork GBM structure consists of fibrils forming pores with diameters slightly less than those of albumin molecules [5][6][7]. This fine meshwork structure is considered to be a critical size barrier impeding ultrafiltration of serum protein molecules in the glomerulus [8][9][10].…”
Section: Introductionmentioning
confidence: 99%